The miR169b/NFYA1 module from the halophyte Halostachys caspica endows salt and drought tolerance in Arabidopsis through multi-pathways - Ji, Jieyun; Zeng, Youling; Zhang, Suwei; Chen, Fangyuan; Hou, Xianfei; Li, Qiang (Frontiers in Plant Science, 2023)
Salt and drought are the major abiotic stress factors plaguing plant growth, development and crop yields. Certain abiotic-stress tolerant plants have developed special mechanisms for adapting to adverse environments in the long process of evolution. Elucidating the molecular mechanisms by which they can exert resistance to abiotic stresses is beneficial for breeding new cultivars to guide agricultural production. Halostachys caspica, a perennial halophyte belonging to Halostachys in Amaranthaceae, is extremely tolerant to harsh environments, which is commonly grown in the saline-alkali arid desert area of Northwest, China. However, the molecular mechanism of stress tolerance is unclear. Nuclear Factor Y-A (NFYA) is a transcription factor that regulates the expression of downstream genes in plant response to adverse environments. It has also been reported that some members of the NFYA family are the main targets of miR169 in plants. In this study, we mainly focused on exploring the functions and preliminary mechanism of the miR169b/NFYA1 module from H. caspica to abiotic stress. The main results showed that RLM-RACE technology validated that HcNFYA1 was targeted by HcmiR169b, qRT-PCR revealed that HcmiR169b was repressed and HcNFYA1 was induced in the H. caspica branches under various abiotic stress as well ABA treatment and Arabidopsis stable transformation platform with molecular methods was applied to elucidate that the HcmiR169b/HcNFYA1 module conferred the salt and drought tolerance to plants by enhancing ABA synthesis and ABA signal transduction pathways, maintaining ROS homeostasis and the stability of cell membrane. HcNFYA1 is expected to be a candidate gene to improve plant resistance to salt and drought stresses.